Epidemiologi, Patofisiologi, dan Faktor Resiko Human Papilloma Virus - Risma Nurjanah; Nurul Halisa; Wulan Pertiwi (Jurnal Biodiversitas dan Bioteknologi, 2024)
Human Papillomavirus is a type of virus that mostly infects the reproductive tract. Men and women who have high sexual activity have a greater chance of being infected with this virus. HPV is a virus that causes many cancers, one of which is cervical cancer which is one of the main causes of death in cancer patients. HPV infection is a serious problem, especially for poor and developing countries, because poverty and laziness are the main causes of the spread of sexually transmitted diseases. One form of prevention that is widely used in various countries is the HPV vaccine program.